Models and technologies of political risk management: political-theoretical aspect - K. K. Pozdnyakov (Современная наука и инновации, 2025)
This article presents various points of view of foreign and domestic political scientists devoted to the study and analysis of political risks. The author presents the entire spectrum of theoretical definitions of the definition of "political risk", proposing to consider political risks not only as a source of negative impact, but also from the point of view of new opportunities and resources for business development. The author's point of view is presented, which considers political risks as events occurring in the political environment associated with the actions of the government and influencing political processes. As a result, basic ideas about the main parameters of political risks as a special phenomenon in international relations are formed: complexity, inconsistency, manifestation in various aspects of life, etc.